Which score is adequate: Approximation to the assessment rationale used in a Science through English CLIL written test - Miquel Àngel Fuentes (Universitat Autònoma de Barcelona, 2013)
Despite the surge of Content and Language Integrated Learning (CLIL) studies in many areas, assessment practices in CLIL contexts are considered to be much unaccounted for (Poisel, 2007; Hönig, 2009, Maggi, 2012). This paper intends to become a contribution to this area and addresses the issue by approaching to the case study of a Science through English CLIL unit implemented on a state-funded secondary school in Barcelona, Spain. The paper focuses on the written test of the unit and analyzes the students’ responses and degree of satisfaction of the teacher after implementing and correcting the test, which provides valuable insights in the light of teacher development and offers a snapshot of CLIL assessment practices and their effects. The results present a close look at the teacher’s attitude towards content and language errors and points out the lights and shadows of assessment in CLIL while highlighting the need of disclosing further assessment practices in similar contexts.